2018
DOI: 10.5194/bg-15-5909-2018
|View full text |Cite
|
Sign up to set email alerts
|

Coastal primary productivity changes over the last millennium: a case study from the Skagerrak (North Sea)

Abstract: Abstract. A comprehensive multi-proxy study on two sediment cores from the western and central Skagerrak was performed in order to detect the variability and causes of marine primary productivity changes in the investigated region over the last 1100 years. The cores were dated by Hg pollution records and AMS 14C dating and analysed for palaeoproductivity proxies such as total organic carbon, δ13C, total planktonic foraminifera, benthic foraminifera (total assemblages as well as abundance of Brizalina skagerrak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Due to an increased area of connection with the North Sea under higher sea levels, the Kattegat, Limfjord and Danish coastal waters receive greater input of (nutrient rich) highly oxygenated marine water from the Skagerrak/North Sea, increasing both salinity and productivity within these waters. Higher palaeoproductivity has also been documented in Skagerrak sediments during warmer periods such as the Medieval Climate Anomaly and associated with the positive state of the North Atlantic Oscillation (NAO) 50 . The long-term history of the NAO remains equivocal, though conditions consistent with a predominately positive NAO state, particularly increased storminess, higher sea levels and higher temperatures across northwest Europe 51 , have been inferred over the HTM 52,53 , and could Environmental variables: a Pollen-inferred mean annual air temperature based on a sediment succession from Lake Trehörningen 37 , southwest Sweden and examples of warmth-demanding indicator species present during the Holocene thermal maximum (HTM), but absent/rare in Danish waters today (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an increased area of connection with the North Sea under higher sea levels, the Kattegat, Limfjord and Danish coastal waters receive greater input of (nutrient rich) highly oxygenated marine water from the Skagerrak/North Sea, increasing both salinity and productivity within these waters. Higher palaeoproductivity has also been documented in Skagerrak sediments during warmer periods such as the Medieval Climate Anomaly and associated with the positive state of the North Atlantic Oscillation (NAO) 50 . The long-term history of the NAO remains equivocal, though conditions consistent with a predominately positive NAO state, particularly increased storminess, higher sea levels and higher temperatures across northwest Europe 51 , have been inferred over the HTM 52,53 , and could Environmental variables: a Pollen-inferred mean annual air temperature based on a sediment succession from Lake Trehörningen 37 , southwest Sweden and examples of warmth-demanding indicator species present during the Holocene thermal maximum (HTM), but absent/rare in Danish waters today (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, there exist significant uncertainties in both the earlier estimates and in our 210 Pb-based calculations. Furthermore, previous studies indicated substantial temporal variability of primary production rates in the Skagerrak (Binczewska et al, 2018;Louchart et al, 2022). Hence, a more comprehensive approach, such as the application of organic carbon diagenetic modeling, is required to constrain the role of primary production in the local sediment input.…”
Section: Proportions Of Local and Lateral 210 Pb And Sediment Inputsmentioning
confidence: 95%